Rosuvastatin Alleviates Intestinal Injury by Down-Regulating the CD40 Pathway in the Intestines of Rats Following Traumatic Brain Injury - Hu, Yangchun; Wang, Xiaojian; Ye, Lei; Li, Chao; Chen, Weiwei; Cheng, Hongwei (Frontiers in Neurology, 2020)
Statins have been reported to suppress CD40 expression and nuclear factor (NF)-κB activation, which are both up-regulated in the intestines following traumatic brain injury (TBI)-induced intestinal injury. In this study, we aimed to investigate the effects of the statin rosuvastatin on post-TBI jejunal injury in rats, focusing on potential mechanisms involving the CD40/NF-κB signaling pathway. The jejunal CD40 expression was determined by western blotting. The DNA-binding activity of NF-κB was assessed by electrophoretic mobility shift assays (EMSAs). The tumor necrosis factor (TNF)-α and interleukin (IL)-1β levels were assessed by enzyme-linked immunosorbent assays (ELISAs). The severity of the jejunal mucosal injury was assessed by hematoxylin and eosin (HE) staining and histopathological evaluation. We found that the post-TBI upregulation of both CD40 expression and NF-κB activity in the jejunal tissues were significantly inhibited by rosuvastatin, while the post-TBI expression of TNF-α and IL-1β was significantly suppressed by rosuvastatin. In addition, rosuvastatin significantly ameliorated TBI-induced effects on the villus height, crypt depth, and villous surface area. Rosuvastatin suppressed TBI-induced intestinal injury in rats, which may be associated with the blockade of the CD40/NF-κB pathway.